Apical and periapical tissues responses after root canal obturation with two calcium hydroxid based sealers in dog’s teeth - Maria Renata Giazzi NASSRI; Antonio Carlos BOMBANA; Raphael Carlos Comelli LIA (Revista Sul-Brasileira de Odontologia, 2009)
Introduction: At the ending of endodontic treatment, is very important that the choice of root canal’s sealer will be done by biological compatibility criterial, which could promote less inflammation, turning quicker and more effective the healing process. Objective and methodology: The aim of this study was to evaluate the apical and periapical tissues reactions in dog’s teeth, after pulpectomy and root canal’s cleaning and shaping, which limit was the fisiological barrier of delta apical, and filling with gutta-percha and two calcium hydroxide based endodontics sealers, Sealapex® and Apexit®, by those hystopatological events in observation periods of 7, 21 and 45 days, making a comparison of inflammatory reactions and reparacional evolution that both materials promoted. Past all periods, the dogs were killed and histological cuts of teeth were obtained. Results: Through qualitative-quantitative analysis, Sealapex showed inflammatory level among mild and moderate in all periods, having a great improvement in healing process at 45 days. There was a biggest dispersion of Apexit in periapical tissue, which caused an intense macrophage activity, raising inflammatory level in last period. Conclusions: Regardless of the sealer used, there were observed necrosis in a few of delta apical’s ramifications, being mostly in tooth filling by Apexit. In both ways, Sealapex showed best results than Apexit, about increased inflammatory reaction and healing process.